2009
DOI: 10.1021/cg801178m
|View full text |Cite
|
Sign up to set email alerts
|

Cocrystals of Caffeine and Hydroxybenzoic Acids Composed of Multiple Supramolecular Heterosynthons: Screening via Solution-Mediated Phase Transformation and Structural Characterization

Abstract: Caffeine, a pharmaceutical model compound, generally forms cocrystals with carboxylic acids that involve an O-H • • • N hydrogen bond between the carboxylic acid group of the acid and the caffeine imidazole moiety. Such solids are typically based on a single heterosynthon. To examine the facility of introducing additional supramolecular heterosynthons to the caffeine-carboxylicacid cocrystal system, structural isomers of aromatic carboxylic acids (i.e., hydroxy-and dihydroxybenzoic acids) with additional hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
130
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 119 publications
(136 citation statements)
references
References 60 publications
6
130
0
Order By: Relevance
“…It was also known that CA-HY existed as 1 : 2 and 2 : 1 co-crystallization systems. 29) According to the previous report, the lattice energy of CA-HY (1 : 2) was lower than that of CA-HY (2 : 1), 30) suggesting that CA-HY (1 : 2) was more stable than CA-HY (2 : 1). Therefore, CA-HY (1 : 2) was used in the following study.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…It was also known that CA-HY existed as 1 : 2 and 2 : 1 co-crystallization systems. 29) According to the previous report, the lattice energy of CA-HY (1 : 2) was lower than that of CA-HY (2 : 1), 30) suggesting that CA-HY (1 : 2) was more stable than CA-HY (2 : 1). Therefore, CA-HY (1 : 2) was used in the following study.…”
Section: Resultsmentioning
confidence: 90%
“…The PXRD patterns of the co-crystals obtained in this study were identical to those reported previously. [26][27][28][29] It was previously reported that CA-MA existed as 1 : 1 and 2 : 1 co-crystallization systems. 28,29) However, we found that CA-MA (2 : 1) changed to CA-MA (1 : 1) upon the presence of equimolar MA, suggesting that CA-MA (1 : 1) is more stable than CA-MA (2 : 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Zhang's group [171,172] described nine cocrystals involving caffeine and structural isomers of (di)hydroxybenzoic acids. The cocrystals are studied using a new technique which is based on thermodynamically driven solution-mediated phase transformation (SMPT).…”
Section: Molecular Recognition Of Caffeine With Polyphenols and Carbomentioning
confidence: 99%
“…The latter finding led the authors to speculate on the proper nomenclature that would be suitable for crystal systems containing neutral and charged organic compounds contained in the same structure. Nine cocrystal products have been obtained by the interaction of caffeine with 2-hydroxy, 3-hydroxy, and 4-hydroxybenzoic acids, and also with 2,3-dihydroxy, 2,4-dihydroxy, 2,5-dihydroxy, 3,4-dihydroxy, and 3,5-dihydroxybenzoic acids [40]. The existence of OÀH(carboxyl)Á Á ÁN (imidazole), OÀH(hydroxyl)Á Á ÁO(urea), and OÀH(hydroxyl)Á Á ÁO(amide) heterosynthons was reported in the structurally diverse cocrystals, which were produced using a thermodynamically driven, solution-mediated, phase transformation process.…”
Section: Cocrystal Systems Formed By Carbamazepinementioning
confidence: 99%